CERITA RAKYAT SALAH SATU MEDIA PEMBELAJARAN SASTRA ANAK LINTAS KURIKULUM - Aida Azis, Sitti (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2014)
In its capacity as a cultural heritage, folklore contained with positive ideas, noble thoughts, and valuable life experience. Therefore, folklore can be selected as the learning media of children’s literature across curriculum. To take advantage of folklore as a medium, it is necessary to take note about the functions contained in the selected stories. Those functions need to be contextualized within or to be accrossed to the other subject matters, for example Indonesian Language, Religious Education, Civic Education, Mathematics, Science, and Social Studies. The character figures in Dada Ema (folklore of South Sulawesi) in line with the low and high grade of core basic competency, ie: having honest behavior, discipline, responsibility, polite, caring, confident in interacting with family, friends, neighbors, and teachers.